Effects of atmospherics on emotions and intention with respect to involvement under different shopping environments - Loureiro, S. M. C.; Koo, D.-M.; Ribeiro, L. (Journal of Global Scholars of Marketing Science, 2013)
The present study deals with the S-O-R framework. The past five decades of research have successfully validated the S-O-R model in offline and online contexts. However, there is still room for improvement. In particular, hedonic aspects have been proposed as distinctive aspects to differentiate companies from their competitors. Previous researchers have (1) been somewhat reluctant to investigate dominance and other emotional responses, and (2) produced mixed results regarding the impact of atmospherics and emotional responses on behavior. Building on this tradition of research, this study investigates the S-O-R model by incorporating delight as an additional emotional response and tests the moderating effects of consumers' involvement and shopping environments (three-way interactional effects) in connection with the links among atmospherics, emotions, and intentions. The current findings demonstrate that the model fit better for low-involvement consumers than for high-involvement consumers. This was true for both offline and online environments. The results show that layout and information are two important factors in pleasing and arousing consumers, especially in the case of low-involvement consumers, and that delight is determined by both arousal and pleasure but is a determinant of both intention and word-of-mouth only for consumers with low involvement, whether they are in offline or online environments. The theoretical and practical implications are discussed in the conclusion.